(untitled) (Canadian Dermatology Today, 2022)
Atopic dermatitis (AD) is a chronically relapsing inflammatory skin disease, affecting 15-20% of people in developed countries. It affects approximately 20% of the pediatric population and 5-10% of adults, as either adult-onset AD or as persistent AD from childhood. It can significantly affect quality of life through its symptoms, the appearance of the skin, the impact of treatment, and secondary infections. The management of AD may be complicated by its multifactorial and heterogeneous disease presentation that is affected by both genetic and environmental factors. While there is a strong association between AD and other atopic conditions such as asthma, allergic rhinitis, and food allergies, which share similar pathophysiological pathways, this relationship is not yet fully understood. A predisposition for immunoglobulin E (IgE)-mediated responses to environmental stimuli appears to be the common denominator between these conditions. A recent Delphi process identified unmet needs in three main areas of AD management: (i) diagnosis, (ii) management and prognosis, and (iii) treatment. Regarding diagnosis, it was determined that AD can be challenging to diagnose, particularly in adults or when confined only to the hands, and that validated diagnostic criteria are lacking. Regarding management and prognosis, the consensus panel noted that while AD was a clinical diagnosis, there were no standardized laboratory tests and reliable biomarkers to establish diagnosis in difficult cases, to stratify for severity or to monitor treatment efficacy. Highlighting the need for effective treatments for AD, the consensus panel developed fifteen statements in the area of treatment.